Association between paternal involvement in childcare and child injury: the Japan Environment and Children’s Study (JECS) - Kanako Shimada; Akiko Tsuchida; Haruka Kasamatsu; Tomomi Tanaka; Kenta Matsumura; Hidekuni Inadera; the Japan Environment and Children’s Study Group (BMC Pediatrics)
Abstract Background Previous studies have demonstrated that paternal involvement in childcare for infants up to 6 months of age can prevent injuries in children up to 18 months of age. However, the relationship after 18 months of age has not been clearly established. Therefore, this study investigated the association between paternal involvement in childcare at 6 months of age and injuries in children between birth and 4 years of age. Methods This study analysed data from 72,343 children and mothers who participated in the Japan Environment and Children’s Study (JECS). Seven items of paternal involvement in childcare at 6 months of age—indoor play, outdoor play, feeding the child, diaper changing, dressing, bathing, and putting the child to bed—were assessed using a 4-item Likert-type scale. The total score was calculated from the responses (0–21) and divided into three tertiles: low (0–11), middle (12–14), and high (15–21). Children were asked about trauma and burn injuries occurring from birth to 4 years of age. Multivariable logistic regression analysis was performed to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Results The incidence of traumatic injury in children from birth to 4 years of age was 5.0%, and the incidence of burn injury was 4.0%. The association of trauma and burn with the risk of child injury by tertile of paternal involvement in childcare at 6 months of age showed a protective effect for trauma (P for trend = 0.013). Responses of ‘seldom’ ‘sometimes’, or ‘all the time’ to the items playing at home, playing outdoors, feeding, bathing, and putting the child to sleep were more likely to be associated with a lower risk of trauma in children compared with responses of ‘never’. There was no association between paternal involvement in childcare and burn injuries in children. Conclusions Paternal involvement in childcare at 6 months of age was associated with a lower risk of trauma in children, and a protective effect against traumatic injuries was shown in 5 of the 7 items of paternal involvement in childcare.